Analisis Efektivitas Antiemetik Tunggal vs. Kombinasi dalam Menurunkan Kejadian PONV Pasca Anestesi Umum: Scoping Review - Syafrina Rossa; Nafitsa Tazkya Zukri; Nadiya Ingka Oktavia; Adnan Akbar Prawira; Elldya Septiani Pramita (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Postoperative nausea and vomiting (PONV) is one of the most common complications following surgery under general anesthesia, with an incidence of 20–70% in the general population and exceeding 80% in high-risk patients. PONV can reduce patient comfort, delay recovery, and increase the risk of dehydration, electrolyte imbalance, and surgical wound dehiscence. This article aims to analyze the effectiveness of single antiemetic therapy compared with combination antiemetic therapy in reducing the incidence of PONV in adult patients after general anesthesia, based on evidence from randomized controlled trials (RCTs). This study applied the Arksey and O’Malley framework for analysis. Literature was obtained from ScienceDirect, PubMed, and the Cochrane Library, published between 2020 and 2025. Identification and selection of studies followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines (Moher et al., 2009). A total of 10 articles were included and analyzed, focusing on outcomes such as the incidence of nausea and vomiting, complete response rates, and the need for rescue antiemetic therapy. The findings indicate that single antiemetic therapy remains effective in low-risk patients, whereas combination antiemetic therapy with multiple mechanisms of action provides more optimal protection, particularly in high-risk patients. These results provide an evidence-based foundation for healthcare professionals in selecting the most effective PONV prevention strategies according to individual patient risk and clinical conditions.